2003
DOI: 10.1038/nature01625
|View full text |Cite
|
Sign up to set email alerts
|

Detection of bromine monoxide in a volcanic plume

Abstract: The emission of volcanic gases usually precedes eruptive activity, providing both a warning signal and an indication of the nature of the lava soon to be erupted. Additionally, volcanic emissions are a significant source of gases and particles to the atmosphere, influencing tropospheric and stratospheric trace-gas budgets. Despite some halogen species having been measured in volcanic plumes (mainly HCl and HF), little is known about bromine compounds and, in particular, gas-phase reactive bromine species. Such… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

10
294
3
1

Year Published

2004
2004
2015
2015

Publication Types

Select...
9
1

Relationship

4
6

Authors

Journals

citations
Cited by 354 publications
(319 citation statements)
references
References 23 publications
10
294
3
1
Order By: Relevance
“…This is highly significant, as anthropogenic sulphate is presently considered to be the most important factor offsetting the anthropogenic greenhouse effect. Recently, USB2000s have been adapted for remotely sensed measurements of two other volcanogenic gases: NO 2 and BrO (Bobrowski et al 2003). The former observation supports a recent report that volcanoes may have played a significant role in generating biologically available forms of nitrogen, via thermal fixation, during the evolution of the early Earth (Mather et al 2004).…”
Section: Observationssupporting
confidence: 62%
“…This is highly significant, as anthropogenic sulphate is presently considered to be the most important factor offsetting the anthropogenic greenhouse effect. Recently, USB2000s have been adapted for remotely sensed measurements of two other volcanogenic gases: NO 2 and BrO (Bobrowski et al 2003). The former observation supports a recent report that volcanoes may have played a significant role in generating biologically available forms of nitrogen, via thermal fixation, during the evolution of the early Earth (Mather et al 2004).…”
Section: Observationssupporting
confidence: 62%
“…Fourier-transform interferometers (FT-IRs) have become a very valuable device for volcanic gas studies (Love et al, 1998;Oppenheimer et al, 1998;Burton et al, 2000;Horrocks, 2001), including measurements of gas ratios reported by Oppenheimer et al (2002). Systems using ultraviolet light as a source have recently been developed for volcanic SO 2 measurements (McGonigle, 2005;Horton et al, 2006), for volcanic BrO measurements (Bobrowski et al, 2003), and also for CO 2 slantpath columns (Goff et al, 2001). More recently Stremme et al (2013) and Krueger et al (2013) presented measurements of volcanic emissions using a scanning FT-IR, showing two-dimensional visualisations of SO 2 based on thermal emission spectroscopy.…”
mentioning
confidence: 99%
“…In this article we focus on a third potentially significant source of halogens to the atmosphere: volcanic emissions. BrO was detected in a volcanic plume for the first time at Soufriere Hills volcano on Montserrat [Bobrowski et al, 2003], and has subsequently been measured at other volcanoes (a brief description of BrO levels and emissions of five different volcanoes is given by N. Bobrowski and U. Platt (Bromine monoxide studies in volcanic plumes, submitted to Journal of Volcanology and Geothermal Research, 2006, hereinafter referred to as Bobrowski and Platt, submitted manuscript, 2006)). So far BrO has been detected at all volcanoes where the authors carried out measurements at distances exceeding about 1 km.…”
Section: Introductionmentioning
confidence: 99%